Tonga : 2007 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that Tonga's real GDP growth is estimated to turn negative in FY06/07, declining by 3 1\2 percent. The economy will continue to be subject to uncertainty and shocks. While economic growth should return to positive, albeit low, levels in the medium term, there are lingering risks on the policy front that could derail efforts to restore stability, in particular those that might arise from pressures to increase public sector hiring. A further drop in remittances and terms of trade shocks could present significant pressures on official reserves.